Evaluation of Micro, Small And Medium Enterprises (MSMES) Financing Policies For MSME Actors In Yogyakarta - I Gusti Gede Heru Marwanto; Afif Nur Rahmadi; Nonni Yap (PT. Publikasiku Academic Solution, 2023)
The purpose of this study is to analyze financing policies for Micro, Small and Medium Enterprises (MSMEs) in the Special Region of Yogyakarta. Because MSMEs are the type of economic activity that is most widely carried out by the Indonesian people as a fulcrum in obtaining income for their survival. The role of MSMEs in the Indonesian economy is not only as an absorber of labor because the percentage reaches 90% when compared to large businesses, but also able to introduce various local products to the international world. The type of research carried out is qualitative research with descriptive analytical methods, descriptive data analysis. The results showed that the development of MSME business actors showed an increase. The main obstacles faced by MSME actors are limited business management and fear of taking risks. The lack of coaching and involvement of related agencies is also considered as a factor in the slow development of their business. However, the role of the government is needed in the sustainability and improvement of MSMEs in Yogyakarta.